Peran LPNS Dalam Peningkatan Mutu Madrasah Diniyah Pondok Pesantren Miftahul Ulum Panyeppen - Abdullah, Moh; Komaruddin, Achmad (LP2M IAI Miftahul Ulum Pamekasan, 2021)
Evaluation of learning / education (education evaluation = al-Taqdir al-Tarbawiy) is one of the important components in Madrasah Diniyah, to evaluate the process of teaching and learning activities (KBM). One of the objectives rather than the existence of LPNS as a specialized institution as an evaluator of the results of teaching and learning activities in the Madrasah Diniyah Madrasah Islamic Boarding School Miftahul Ulum Panyeppen. The Center Hotel The existence of LPNS as an independent institution is tasked with carrying out duties as an assessment of student learning outcomes, has a vital role to improve the quality of madrasah diniyah Islamic Boarding School Miftahul Ulum Panyeppen